A tide that cannot be turned. - Seltzer, Irwin (New Statesman, 2001)
The writer argues that economic self interest is a better indicator of immigration policy than humanitarianism. The corporatization of illegal immigration has given urgency to the immigration debate, and the existence of the welfare state has created a conflict between open-door humanitarian immigration policy and the best interests of a nation's economy. Politicians are under pressure from employers to adopt a more liberal stance on immigration because they need young people to support an increase in the number of retired, even though the middle class object to rapid changes in the “look” of their country and unskilled workers object to the a potential threat to their jobs.